Chromosomal Instability in Various Generations of Human Mesenchymal Stem Cells Following the Therapeutic Radiation - Majid Sadeghi Moghadam; Hosein Azimian; Jalil Tavakol Afshari; Mohammad Taghi Bahreyni Toossi; Najmeh Kaffash Farkhad; Seyed Hamid Aghaee-Bakhtiari (Hindawi Limited, 2023)
Background. Radiotherapy is a crucial treatment for most malignancies. However, it can cause several side effects, including the development of secondary malignancies due to radiation-induced genomic instability (RIGI). The aim of this study was to evaluate genomic instability in human mesenchymal stem cells (hMSCs) at different X-ray radiation doses. Additionally, the study aimed to examine the relative expression of certain genes involved in DNA repair, proto-oncogenes, and tumor suppressor genes. Methods. After extracting, characterizing, and expanding hMSCs, they were exposed to X-ray beams at doses of 0, 0.5, 2, and 6 Gy. Nuclear alterations were evaluated through the cytokinesis-block micronucleus (CBMN) assay at 2, 10, and 15 days postirradiation. The expressions of BRCA1, BRCA2, TP53, Bax, Bcl2, and KRAS genes were analyzed 48 hr after irradiation to evaluate genomic responses to different radiation doses. Results. The mean incidence of micronuclei, nucleoplasmic bridges, and nuclear buds was 4.8 ± 1.6, 47.6 ± 6, and 18 ± 2.6, respectively, in the nonirradiated group 48 hr after the fourth passage, per 1,000 binucleated cells. The incidence of micronuclei in groups exposed to 0.5, 2, and 6 Gy of radiation was 14.3 ± 4.9, 32.3 ± 6.5, and 55 ± 9.1, respectively, 48 hr after irradiation. The expression levels of the BRCA2, Bax, TP53, and KRAS genes significantly increased after exposure to 6 Gy radiation compared to the control groups. However, there was no significant increase in BRCA1 and Bcl2 gene expression in our study. Conclusion. This study demonstrated significant nuclear alterations in the 10 days postirradiation due to the RIGIs that they inherited from their irradiated ancestral cells. While chromosomal instability is a prevalent event in malignant cells, so it seems necessary to optimize radiotherapy treatment protocols for tissues that contain stem cells, especially with IMRT, which delivers a low dose to a larger volume of tissues.